2015
DOI: 10.1016/j.applthermaleng.2015.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of external shading on optimum insulation thickness of building walls in a tropical region

Abstract: Please cite this article as: E. Wati, P. Meukam, M.K. Nematchoua, Influence of external shading on optimum insulation thickness of building walls in a subtropical region, Applied Thermal Engineering (2015), Abstract 7 This study aims to optimize the thicknesses of insulation layers in external walls of 8 continuously used building in a subtropical region according to shade level. The investigation 9 is carried out under steady periodic conditions for various wall orientations using a Simulink 10 model construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…Comakli et al examined OIT for cold provinces (Erzurum, Kars, Erzincan) in Turkey. Kaynakli [16]. Yu et al calculated OIT for four typical cities of Shanghai, Changsha, Shaoguan and Chengdu in China.…”
Section: Introductionmentioning
confidence: 99%
“…Comakli et al examined OIT for cold provinces (Erzurum, Kars, Erzincan) in Turkey. Kaynakli [16]. Yu et al calculated OIT for four typical cities of Shanghai, Changsha, Shaoguan and Chengdu in China.…”
Section: Introductionmentioning
confidence: 99%
“…The study stated that the economic model, which includes cost of energy consumption and cost of insulation material and the cost over a lifetime of 22 years of the building, were used to find optimum insulation thickness, energy saving and payback period, for buildings in Cameroon . Wati et al intended to optimize the thicknesses of insulation layers in external walls of continuously used building in a tropical region according to shade level . Axaopoulos et al determined that the optimum insulation thickness for external walls of different orientation of a piggery building was determined accounting for both the heating and the cooling period .…”
Section: Introductionmentioning
confidence: 99%
“…Although very simple and fast in estimating OIT, the degree-days concept and the subsequent simplified relations, Equations (2) and (3), have been criticized for inconvenience, by ignoring the effect of solar radiation and thermal mass [15,16]. Actually, there are a few other parameters that have also been confirmed as affecting OIT significantly, but are not included yet in the above relations.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers examined alternatively the effect of external surface absorptance [17] and color [18] on OIT. In [16] it was examined the effect of shading on OIT, and demonstrated that full shading may decrease OIT by 3-3.5 cm (for a solar absorptance of 0.6). The significant effect of indoor temperature on OIT was also demonstrated [15], with the latter increasing remarkably with the winter Figure 1.…”
Section: Introductionmentioning
confidence: 99%